STYLISTIC USED IN NORA ROBERTS’ THE PAGAN STONE - Akmal; Sitti Aminah (JLE: Journal of Literate of English Education Study Program, 2021)
This research issabout theeanalysissoffStylisticcUseddin Nora Roberts’ novel The Pagan Stone. It departs from theeresearcher’s willing to know the existence of linguistics features, such as figurative languages in literary works. The research’s objectives aree(1)/to analyze theekindssofffigureeoffspeechhuseddin Nora Roberts’ novel The Pagan Stone, (2) to describeetheetypessofffigureeoffspeechhdominantlyyuseddinntheenovel. The method used in this research is qualitative method. The sources of dataainfthissresearchhwereetheenovel entitled The Pagan Stoneewrittennbyy NoraaRobertsspublisheddinn20088anddsomeebooks, journals, and written sources wereeuseddtooanalyzeeand support this research. The instrument used in collecting the data wasdnoteetaking. In analyzing the data, the writer used Perrine’s theory about the figure of speech. In this research, the writer found five types of figure of speech in the novel The Pagan Stone written by Nora Roberts. They are simile, personification, metonymy, repetition, and overstatement. The most dominant type of figure of speech used in the novel is simile, it appears nineteen times, and the less type of figure of speech used in the novel is metonymy, the researcher only found out one from all the data. The implication of this research is to give understanding on the term of figure of speech as one of categories of stylistics to readers whom would like to know more about it.